Taguchi optimization of tribological properties and corrosion behavior of self-lubricating Al–Mg–Si/MoS2 composite processed by powder metallurgy - Kumar, Neeraj; Sharma, Ashutosh; Manoj, M. K.; Ahn, Byungmin (Journal of Materials Research and Technology, 2023)
Self-lubricating aluminum matrix composites (AMCs) can be used to reduce the wear and coefficient of friction (COF) in automotive engine components in which the use of liquid lubricants is not desirable. High temperatures accelerate the oxidation and thermal degradation of a liquid lubricant. In this study, we used powder metallurgy (PM) technique to prepare self-lubricant (MoS2)-based Al–Mg–Si AMCs, designated as Al–Mg–Si–xMoS2 (x in wt.%; x = 1.5, 2.0, 30, 3.5, and 4.0). The dry sliding wear properties were assessed using a pin-on-disk tribometer at various applied loads (20–50 N) and sliding distances (1000–3000 m), based on the Taguchi model (L9). Furthermore, electrochemical corrosion tests such as open circuit potential (OCP) and potentiodynamic polarization (PDP) were performed in a 3.5 wt% NaCl medium. The morphology of the Al–Mg–Si–xMoS2 composites was observed through scanning electron microscopy and energy dispersive spectroscopy to clarify the particle distribution and chemical composition. The results indicated that the addition of MoS2 to Al–Mg–Si decreased the wear and COF and increased the corrosion resistance, compared with those of the pristine Al–Mg–Si matrix alloy under same operating conditions. As the sliding distance increased to 250 m, the COF fluctuated, but it stabilized as the distance approached 3000 m. The effects of the load and reinforcement concentration were more significant than those of the sliding distance and track diameter, as predicted by the Taguchi model and analysis of variance methods.
Keywords: Al-Mg-Si; Aluminium matrix composites; Automotive engine; Coefficient of frictions; Corrosion behaviour; Liquid lubricants; Self-lubricating; Sliding distances; Taguchi optimizations; Tribological properties; Aluminum matrix composite; Corrosion; MoS2; Powder metallurgy; Tribology